2012
DOI: 10.1371/journal.pone.0049711
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characterization, and Function Analysis of the Cactus Gene from Litopenaeus vannamei

Abstract: The nuclear factor-kappa B (NF-κB) pathways play important roles in innate immune responses. IκB is the main cytoplasmic inhibitor of NF-κB. In this study, we identified the LvCactus gene from Litopenaeus vannamei, which is the first cloned IκB homologue in subphylum Crustacea. LvCactus contains six predicted ankyrin repeats, which show similarities to those of Cactus proteins from insects. LvCactus localizes in cytoplasm and interacts with LvDorsal, an L. vannamei homologue to Drosophila melanogaster Dorsal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 50 publications
5
43
0
Order By: Relevance
“…Genome walking libraries were constructed by GenomeWalker™ Universal Kit (Clontech, Japan) according to the previous study [23]. The first round of genome walking PCR amplifications were performed using the primer pair of AP1/5 0 GW-LvJAK-1.…”
Section: Genome Walkingmentioning
confidence: 99%
“…Genome walking libraries were constructed by GenomeWalker™ Universal Kit (Clontech, Japan) according to the previous study [23]. The first round of genome walking PCR amplifications were performed using the primer pair of AP1/5 0 GW-LvJAK-1.…”
Section: Genome Walkingmentioning
confidence: 99%
“…It has been known that NF-kB can upregulate the expression of IkB, and thus in turn attenuate the activation of NFkB itself (58). In L. vannamei, solid evidence has also supported that Dorsal could bind the promoter of Cactus to enhance its expression, thus constituting a negative feedback loop to regulate Dorsal activity (19). In this study, we also observed that the mRNA level of Cactus was increased after the miR-1959 mimics injection and decreased after the inhibitors injection.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the main components of the TLR/NF-kB pathway, including three TLRs, two Tubes (homolog of IRAK4), Pelle (homolog of IRAK1), Myd88, TRAF6, Dorsal (homolog of NF-kB), Cactus (homolog of IkB), and so on, have been systemically studied in L. vannamei. This provides a basis for further investigation of the regulatory mechanism of shrimp immunity and establishes L. vannamei as a useful platform for studying the invertebrate NF-kB pathway (16)(17)(18)(19)(20).…”
mentioning
confidence: 83%
See 2 more Smart Citations